New forms of digital power on the web: dimensions of the sexual politics of Big Tech - Águeda Gómez Suárez; Rosa Mª Verdugo Matés (Revista CIDOB d'Afers Internacionals)
Although it initially appeared that the Internet would be a universal, decentralised, horizontal and egalitarian space, it has ultimately evolved into an ecosystem of vast domains controlled by major tech corporations. This new form of digital power manifests a specific “sexual politics” that primarily extends through leisure, culture, consumption and virtual communication channels, which reproduce and naturalise gender disparities, sexism and misogyny. This paper examines how patriarchy operates through gender dynamics by disseminating and proliferating misogynistic and sexist content online (cyber violence, “mainstream pornography”, the sexual exploitation industry, “digital pimping”), deploying a strategy aimed at consolidating its power, perpetuating sexual hierarchy and the “monetisation of misogyny” within the framework of a specific socio-sexual order.